Breathing Coloniality: An ethnographic case study of language and literacy ideologies and colonial power relations in the positioning and development of 1st generation black children's learning experiences in and outside school contexts - Manganyi-Tawana, Amani Khensani (School of Education, 2022)
This study was inspired by the under theorization of language shifts and the impact that coloniality and language and literacy ideologies have among first generation black children's attending English medium schools positioning and family language planning. I draw on the theoretical framework of [de]coloniality with a particular focus on coloniality of power and the colonial matrix of power in post-colonial South African education and society. I additionally drew upon language ideology and the pedagogization of literacy as conceptual frameworks that helped to investigate the correlation between macro-level discourses that distribute particular types of hegemonic language and literacy ideologies and their effect on the positioning and self-imaging of people from non-mainstream populations. Data was collected through semi-structured interviews with parents and literacy instructors around observed practices and views on language use. In relation to language, my analysis revealed a strong correlation between exclusionary anglonormative language ideology and Standard English ideology in the deficit positioning of non-mainstream children in previously white only ex-Model C schools. The study additionally found that Apartheid notions of superiority and inferiority and racial classifications were reproduced in parent discourses around English language varieties valued for their children to use. My findings suggest the need for a meaningful investigation of English language and literacy crisis rhetoric and the positioning of non-mainstream learners. I argue that research into linguistic discursive practices and language ideology in ex-Model C schools will enable the necessary forms of integration requisite in an equity based not assimilatory educational system.